Kepribadian Wajib Pajak, Pelayanan Fiskus, Sanksi Pajak dan Kepatuhan Wajib Pajak - Permana, Indra; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 32 No 5 (2022)DO - 10.24843/EJA.2022.v32.i05.p08, 2022)
Good tax service services must be provided to all taxpayers to increase taxpayer compliance. Tax sanctions are the actions of taxpayers to always obey in paying their obligations. The purpose of this study was to analyze the effect of taxpayer taxes, tax taxes, and tax taxes on tax compliance at KPP Pratama Denpasar Barat. The sample used was 125 respondents. Data was collected through a survey method with a questionnaire instrument. The analysis used is multiple linear regression. The results showed that the personality of the taxpayer, the service of the tax authorities, and tax sanctions had a positive effect on taxpayer compliance. This shows that in improving taxpayer compliance, what must be considered are the internal factors of individual taxpayers, namely personality factors; and external factors, namely good service from the tax authorities, and sanctions for violations of taxation.     Keywords: Taxpayer Personality; Tax Authorities Services; Tax Sanctions; Taxpayer Compliance.